MFN2 mediates ER-mitochondrial coupling during ER stress through specialized stable contact sites - Gottschalk, Benjamin; Koshenov, Zhanat; Bachkoenig, Olaf A.; Rost, René; Malli, Roland; Graier, Wolfgang F. (Frontiers in Cell and Developmental Biology, 2022)
Endoplasmic reticulum (ER) functions critically depend on a suitable ATP supply to fuel ER chaperons and protein trafficking. A disruption of the ability of the ER to traffic and fold proteins leads to ER stress and the unfolded protein response (UPR). Using structured illumination super-resolution microscopy, we revealed increased stability and lifetime of mitochondrial-associated ER membranes (MAM) during ER stress. The consequent increase of basal mitochondrial Ca2+ leads to increased TCA cycle activity and enhanced mitochondrial membrane potential, OXPHOS, and ATP generation during ER stress. Subsequently, OXPHOS derived ATP trafficking towards the ER was increased. We found that the increased lifetime and stability of MAMs during ER stress depended on the mitochondrial fusion protein Mitofusin2 (MFN2). Knockdown of MFN2 blunted mitochondrial Ca2+ effect during ER stress, switched mitochondrial F1FO-ATPase activity into reverse mode, and strongly reduced the ATP supply for the ER during ER stress. These findings suggest a critical role of MFN2-dependent MAM stability and lifetime during ER stress to compensate UPR by strengthening ER ATP supply by the mitochondria.